Internationalization of Malaysian service firms: business strategy and choice of foreign market entry mode - Asgari, M.; Ahmad, S.Z. (2010)

(untitled)
Despite the substantial amount of work undertaken on internationalization to-date, few have placed emphasis on the temporal processes and dynamisms of the international expansion of firms in the services sector. The numerous studies on internationalization from different theoretical and empirical approaches have their origin in manufacturing firms’ perspectives. Recently, the rapid progress in the service sector has attracted many scholars to study the development, progress and behaviour of service firms. Therefore, this paper is a preliminarily investigation of the pattern of, and motives for, business strategy and choice of entry mode made by Malaysian service firms. Being among the fast growing economies in the Asia Pacific region, which mainly relies on the service sector for economic development, many nascent Malaysian service firms are now seeking to expand beyond their national territory. This research proposes to utilize a case study approach through in-depth interviews with key managers/executives in selected Malaysian service firms to explain the internationalization behaviour of these firms. Limitations of the current study and suggestions for future research are presented.